A Review on Verbal Hygiene - Reza Moghaddam Kiya (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present paper aims at introducing “Verbal Hygiene” by Deborah Cameron (1995, 2012) and assessing the quality of its translation into the Persian Language. In her book, Cameron discusses long-standing debates among proponents of two competing perspectives on language use. On the one hand, there are the traditionalist grammarians who contend that any change is undesirable. Accordingly, they seek to prescribe standards for using language. On the other hand, there are the linguists who argue that language is naturally in a state of flux. “Verbal Hygiene” is a term coined by Cameron to refer to all discourses, practices, and measures directed at regulating language. In this paper, the quality of the Persian translation of the book was assessed based on the model proposed by Katharina Reiss for translation criticism (Reiss, 2000), and it was shown that the translation is poor and quite unsatisfactory. Misinterpretation of the source text, incorrect rendering of the concepts and meanings, grammatical calques, lack of fluency, inappropriate equivalents, and intermingling spoken and written styles of language use are among the deviations in the target text.